Interelation of QiyÄs Ushul Nahwi & QiyÄs Ushul Fiqh In Islamic Law Construction Framework - Hasibuan, Anwar Saleh; Siddiq, Ghofar (Law Development Journal, 2020)
QiyÄs in the scope of Islamic scientific studies is not only studied and discussed in the study of UshÅ«l Fiqh science, but also in the study of UshÅ«l Nahwi science it is also studied and discussed about QiyÄs. This article attempts to analyze, study and explain the form of interrelation that occurs between QiyÄs UshÅ«l Nahwi and QiyÄs UshÅ«l Fiqh in relation to Islamic legal constructs by describing the forms of the relationship between the similarities and differences between the two.